Autoimmune progesterone dermatitis presenting as recurrent, marked angioedema‐like lip changes: An unusual presentation of an uncommon problem. (17th April 2020) - Brown, Hilary; Relic, John
Abstract: Autoimmune progesterone dermatitis is a rare condition with varying clinical presentations. We present a case of autoimmune progesterone dermatitis presenting as recurrent, marked angioedema‐like lip swelling without any other skin changes.